Validated RP-HPLC Method for the Determination of Buspirone in Pharmaceutical Formulations. (4th August 2011) - Basaveswara Rao, M. V.; Nagendrakumar, A. V. D.; Maiti, Sushanta; Raja, Guttikonda
Abstract : A simple, selective, linear, precise, and accurate RP-HPLC method was developed and validated for the rapid assay of the Buspirone in tablet dosage form. Isocratic elution at a flow rate of 1.0 mL/min was employed on a symmetry C18 (250 × 4.6 mm, 5 μ m in particle size) at ambient temperature. The mobile phase consisted of water : acetonitrile : methanol 45 : 35 : 20(V/V). The UV detection wavelength was 210 nm, and 20 μ L sample was injected. The retention time for the Buspirone was 7.057 min. The percentage RSD for precision and accuracy of the method was found to be less than 2%. The method was validated as per the ICH guidelines. The method can be successfully applied for the routine analysis of Buspirone in tablet dosage form.